Feasibility of a Value-Based Character Education Evaluation Instrument in Learning at Health Higher Education Institutions - Djusmalinar, Djusmalinar; Hamzah, Syukri; Syafitasari, Juanda; Putri, Poppy Siska (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
This study aims to develop a valid, reliable, and practical value-based character education assessment instrument to support the implementation of character education in Health Colleges. The method used is Research and Development (R&D) with seven stages, namely needs analysis, instrument design, expert validation, initial trials, revision, field trials, and evaluation. The needs analysis was conducted through literature studies, interviews, and observations at Sapta Bakti Health College to identify the main values of character education, such as integrity, responsibility, cooperation, and empathy, which then served as the basis for the development of indicators and instrument formats. The instrument was validated by character education experts and evaluations to ensure content and construct validity. Initial trials on a small number of respondents were used to identify weaknesses in the instrument before revisions were made. Next, the field trial involved Sapta Bakti Health College students with reliability analysis (Cronbach's Alpha) and factor analysis, which showed a Cronbach's Alpha value above 0.8 as an indicator of high reliability. This instrument is also considered practical by lecturers and is expected to be an effective tool in assessing student character development objectively and systematically, as well as encouraging the strengthening of value-based character education in the curriculum.